Reproductive health knowledge and pre-pregnancy contraceptive use among teenage mothers in Molo, Iloilo City - Crisostomo, Jude Anthony; Cuyong, Jesusa; Dala Luma, Louie Anthony; Dino. Mae Thea. (2015.)
Teenage pregnancy is associated with high risk of maternal complications during delivery and pregnancy. Moreover, maternal deaths among teenage mothers became a major public health concern. In the Philippines, increasing trend of teenage pregnancy has been reported and last 2014, Iloilo City Population Office also reported that 22% of the total cases of teenage pregnancy in the city was form the Districts of Molo. Therefore, development of strategies and programs is needed to reduce the rate of teenage pregnancy cases and investigation of teenager?s knowledge on reproductive health and contraception is important in this development. Thus, this study aimed to assess the reproductive health knowledge and pre-pregnancy contraceptive use among teenage mothers in Molo, Iloilo City. The cross-sectional study involved a total of 157 teenage mothers aged 15-19 form the Districts of Molo I and II. An interview survey was administered to the study population and the data was analyzed using SPSS (version 21) software. The study also used T-test, Chi-square and Fishers? exact test as statistical tools for exploratory analysis of the data gathered. Results of the study showed that the reproductive health knowledge of the teenage mothers in Molo was relatively low (µ=0.87) which also attributed to low pre-pregnancy contraceptive use among teenage mothers (21.7%). The most commonly reported reason for non-contraceptive use is they thought that they could not get pregnant at that time (17.4%). Factors influencing low contraceptive use among respondents are significantly related to one?s religion (p=0.004), knowledge on sexually-transmitted infections (p=0.029), discussion of contraceptive use with partner (p=0.021), person shared with personal matters (p=0.017), openness to parents (p=0.011) and reproductive health knowledge score (p=0.028). These findings suggest that reproductive health education should be strengthened and proactive discussions about the use of contraception among teenagers should be encouraged. Family members are also expected to guide the teenagers about this topic. Moreover, validation of the factors that showed significant associations to low contraceptive use through the use of probability sampling techniques and larger sample size is recommended in future studies.
Research Project - Bachelor of Science in Public Health. University of the Philippines Visayas, Miagao,Iloilo
Keywords: Teenage pregnancy; Teenage mothers -- Molo, Iloilo City; Reproduction health knowledge; Sexually-transmitted infections (STI); Contraceptive use -- Pre-pregnancy.